Optimalisasi Pemanfaatan Sumber Daya Alam Berkelanjutan Dalam Era Transisi Energi - Rahmarisa, Faty; Tahir, M.; Surayudin, Nyak (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2025)
In the era of the increasingly urgent energy transition, optimizing the use of sustainable natural resources is a must. The global energy transition towards more sustainable energy sources is both a challenge and an opportunity for countries around the world. Various strategies and approaches that can be applied to achieve these goals. Through data analysis and relevant case studies, it is hoped that effective solutions can be found to overcome the challenges faced in the sustainable use of natural resources